A novel portable extra-corporeal life support system for the treatment of cardio-pulmonary failure under controlled hypothermia. Preliminary study in experimental animals - Benassi, Filippo; Giuliani, Enrico; Corticelli, Davide; Parravicni, Roberto (Acta Biomedica Atenei Parmensis, 2016)
Abstract Purpose: several therapeutic options are used in emergency situations, when heart and/or lung functions acutely fail. Because of the poor results of conventional treatments, the use of an extra-corporeal life support (ECLS) systems able to completely assume the heart and lung functions in emergency situations is becoming a viable alternative. We have developed a unique ECLS system for patients needing extended respiratory and/or circulatory support and controlled hypothermia.  Methods: the ECLS apparatus is portable and easy to handle by incorporating a disposable centrifugal blood pump, a membrane oxygenator, a waterless heating/cooling device. A sensor’s system is integrated in the equipment for continuous monitoring/displaying of several parameters.  Results: the system was tested in bench laboratory studies and in large experimental animals to check feasibility, functionality, durability, consistency and safety. Adult sheep were used, after cannulation of large vessels in the neck, either to test the apparatus in normal physiologic conditions, or under controlled mild hypothermia (33 to 34° C). Two modes of vascular access were tested:  veno-arterial (V-A) and veno-venous (V-V). Vital parameters and systolic blood pressures were continuously monitored up to 48 hours. Discussion: initial laboratory experiment of the He-Art apparatus indicated that the system was safe and able to control and stabilize the hemodynamic conditions. The device represented a second generation ECLS system, by adding the protective effect of moderate to mild hypothermia against ischemic cardiac and brain injuries.